Associations Between Consumption of Coffee and Caffeinated Soft Drinks and Late Stillbirth—Findings From the Midland and North of England Stillbirth Case-Control Study. Issue 6 (June 2021) - Heazell, Alexander E. P.; Timms, Kate; Scott, Rebecca E.; Rockliffe, Lauren; Budd, Jayne; Li, Minglan; Cronin, Robin; McCowan, Lesley M. E.; Mitchell, Edwin A.; Stacey, Tomasina; Roberts, Devender; Thompson, John M. D.
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2021;256:471–477) The prevention of stillbirth is an enduring problem. Identifying risk factors and developing strategies to minimize their effect can help to reduce the prevalence of stillbirth.